2015
DOI: 10.1007/s00410-015-1155-2
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale temporal recovery, reconstruction and evolution of a post-supereruption magmatic system

Abstract: eruption of 25 rhyolitic units starting at ~12 ka. The dacites show strongly zoned minerals and wide variations in meltinclusion compositions, consistent with early magma mixing followed by periods of cooling and crystallisation at depths of >8 km, overlapping spatially with the inferred basal parts of the older Oruanui silicic mush system. The dacites reflect the first products of a new silicic system, as most of the Oruanui magmatic root zone was significantly modified in composition or effectively destroyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
230
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(248 citation statements)
references
References 105 publications
18
230
0
Order By: Relevance
“…Stepwise 170 changes in composition between the SG2 and SG3 rhyolites (Fig. 2) are consistent with 171 5%-10% dissolution of orthopyroxene and plagioclase, liberating compatible trace 172 elements (e.g., Sr, Eu, Zn, Mn, Ti) from the crystals to the melt phase within the crystal 173 mush (Barker et al, 2015). These signatures would only be recorded in the final SG3 174 eruptive products if heating and dissolution occurred in the mush prior to extraction of 175 the crystal-poor rhyolite melt (Fig.…”
Section: Introduction 29mentioning
confidence: 66%
See 3 more Smart Citations
“…Stepwise 170 changes in composition between the SG2 and SG3 rhyolites (Fig. 2) are consistent with 171 5%-10% dissolution of orthopyroxene and plagioclase, liberating compatible trace 172 elements (e.g., Sr, Eu, Zn, Mn, Ti) from the crystals to the melt phase within the crystal 173 mush (Barker et al, 2015). These signatures would only be recorded in the final SG3 174 eruptive products if heating and dissolution occurred in the mush prior to extraction of 175 the crystal-poor rhyolite melt (Fig.…”
Section: Introduction 29mentioning
confidence: 66%
“…The relatively large width of the diffusion profiles investigated in this study means that common problems reported in other studies of convolution and pixel size were not considered to be of significant effect (Morgan et al, 2004;Cooper, 2014 Allan et al, 2013). Average (Av) diffusion model timescales given for parameter estimates of 860 °C, 1.5 MPa and log ƒO 2 of 0.2 ∆NNO from Barker et al (2015). Maximum (Max) and minimum (Min) timescales use uncertainties ±30 ºC or ± 0.3 log units ∆NNO.…”
Section: References Citedmentioning
confidence: 85%
See 2 more Smart Citations
“…Much effort on silicic magma reservoirs has focused on the products of large (10 2 –10 3 km 3 ) eruptions. However, the repeated modest‐volume (<20 km 3 ) eruptions that often precede and follow such events provide a high‐temporal‐resolution sampling of magma reservoirs that can reveal a spatial and temporal thermochemical evolution that may be obscured in voluminous ignimbrites (Bachmann et al, ; Barker et al, ; Metz & Mahood, ; Smith et al, ; Sutton et al, ). Zoned crystals record changing magmatic conditions; moreover, accessory phases with a high affinity for U and Th, such as zircon, allow for the in situ determination of the trace element composition and age within the same crystal domain (e.g., Claiborne, Miller, Flanagan, et al, ; Reid et al, ).…”
Section: Introductionmentioning
confidence: 99%